Building of professional communicative competence in foreign students - Karayel, Sevinc (2021)
The Turkish students who study at Russian universities continue learning Russian at the main departments. The main difficulty which foreign students face while learning Russian is scientific style. Those who teach Russian as a foreign language admit that foreign students are often unprepared to learn specific vocabulary. The article covers a completely different approach for presentation of specific vocabulary, developed by the authors of “Training for professional activity in Russian of “Public Relations” speciality foreign students” (L.V. Adonina, S.V. Lazarev, S.V. Smirnova, O.S. Fisenko).